Evaluating the suitability of Brazilian native species for riverbank stabilization and protection - Wolff Kettenhuber, Paula Letícia; Sutili, Fabrício Jaques (Revista Brasileira de Engenharia de Biossistemas, 2024)
In Brazil, soil and water bioengineering techniques have mainly been used for hydraulic stabilization, water course management and to re-establish the vegetation in fluvial environments. In these techniques plants are considered as an important structural component and their use requires adequate selection. The present study aimed to evaluate the root system and shoot development traits of the Allamanda cathartica L., Ludwigia elegans (Camb.) H. Hara and Sesbania virgata (Cav.) Pers species. The experiment was conducted in a greenhouse at the Laboratory of Soil Bioengineering at the Federal University of Santa Maria. The following variables were evaluated after 120 days: the survival rate, average height, average root collar diameter, average number and sum of shoot length per plant, average number of primary roots and the sum of primary root length, length of the largest root and root dry mass per plant. The percentage of fine roots and coarse roots and distribution of root dry mass percentage in soil depth were also evaluated. The results confirm the suitability of the L. elegans, S. virgata and A. cathartica species for riverbank stabilization and protection in soil and water bioengineering works.